EXAMINING THE EVOLUTION AND TRANSITION OF URDU AS THE LINGUA IN PAKISTAN: A SCHOLARLY INVESTIGATION INTO LANGUAGE CHANGE AND SHIFT - Muhammad Atif; Dr. Aftab Akram (International Journal of Contemporary Issues in Social Sciences, 2024)
The research was conducted to find out the change and shift that took place in the Urdu language. A lot of space has been found to explore the transformation in language because people have done much to change language at the lexical and transcript levels in the last few years. The study explained historical, cultural, and economic conditions, and government policies and also explored people’s behaviour and social media impact on the language. This study uncovered different reasons for the change in Urdu and the lingua franca of Pakistan and the approach of particularly the futuristic language user. The researcher adopted a mixed method approach to analyze the data taken from educated people in society about the current usage of the language compared it with the past and used it for future prediction. The people with expertise in Urdu, for example, M.Phil scholars and PhD. scholars were also the participants in this research. The researcher recorded their views through mobile phones while asking questions about the Urdu language shift and change. Many aspects of the language change and shift have been discovered through their opinions. Experts warned that if the proper steps were not taken urgently, the language, especially the writing style, might be completely damaged and our new generations would not be able to understand the past literature of Urdu. People related to the research may find how Facebook, WhatsApp, Instagram etc. are making changes to the script of the Urdu language.